"Now that you are circumcised, you cannot have first sex with your wife": post circumcision sexual behaviours and beliefs among men in Wakiso district, Uganda. Issue 1 (5th June 2017) - Kibira, Simon Peter Sebina; Atuyambe, Lynn Muhimbuura; Sandøy, Ingvild Fossgard; Makumbi, Fredrick Edward; Daniel, Marguerite
Abstract: Introduction : Safe male circumcision is an important biomedical intervention in the comprehensive HIV prevention programmes implemented in 14 sub‐Saharan African countries with high HIV prevalence. To sustain its partial protective benefit, it is important that perceived reduced HIV risk does not lead to behavioural risk compensation among circumcised men and their sexual partners. This study explored beliefs that may influence post circumcision sexual behaviours among circumcised men in a programme setting. Methods : Forty‐eight in‐depth interviews were conducted with newly circumcised men in Wakiso district, central Uganda. Twenty‐five men seeking circumcision services at public health facilities in the district were recruited from May to June 2015 and, interviewed at baseline and after 6 months. Participants' beliefs and sexual behaviours were compared just after circumcision and at follow up to explore changes. Data were managed using atlas.ti7 and analysed following a thematic network analysis framework. Results : Four themes following safe male circumcision emerged from this study. Beliefs related to: (1) sexual cleansing, (2) healing, (3) post SMC sexual capabilities and (4) continued HIV transmission risk. Most men maintained or adopted safer sexual behaviour; being faithful to their partner after circumcision or using condoms with extramarital partners following the knowledge that there was continued HIV risk post circumcision. The most prevalent risky belief was regarding sexual cleansing post circumcision, and as a result of this belief, some men had one off condom‐less sexual intercourse with a casual partner. Some resumed sex before the recommended period due to misunderstanding of what comprised healing. Conclusions : Although most men maintained or adopted safer sexual behaviour, there were instances of risky sexual behaviour resulting from beliefs regarding the first sexual intercourse after circumcision or misunderstandings of what comprised wound healing. If not addressed, these may attenuate the safe male circumcision benefits of risk reduction for HIV.